2005
DOI: 10.1603/0022-0493-98.4.1369
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Resistance to <I>Callosobruchus maculatus</I> (Coleoptera: Bruchidae) in Mungbean Variety VC6089A and Its Resistance-Associated Protein VrD1

Abstract: Characteristics of resistance of VC6089A, a mungbean, Vigna radiata (L.) Wilczek, bred by using a wild Vigna species, V. sublobata (Roxburgh) Verdcourt (accession no. TC1966), and containing a novel protein, VrD1, were investigated against the cowpea weevil, Callosobruchus maculatus (F.). The seeds of VC6089A showed high level of resistance; > 96% of the bruchid eggs failed to develop into adults, whereas 85% of eggs laid on susceptible cultivar VC1973A became adults. Mortality of surviving bruchids raised for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Recently, [ 13 ] confirmed the presence of resistance genes against bruchids on chromosome 5 of TC1966. In mungbean line VC6089A, which was bred by using TC1966 as a resistance source, a protein putatively having polysaccharide hydrolase activity termed VrD1 was isolated, which inhibited the development of C. maculatus into adults when used in artificial seeds [ 14 ]. A 4-week feeding study on mice comparing a commercial mungbean line with an isogenic line containing the bruchid resistance gene from TC1966 showed no negative impact on growth or any pathological effect of the V. radiata var.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, [ 13 ] confirmed the presence of resistance genes against bruchids on chromosome 5 of TC1966. In mungbean line VC6089A, which was bred by using TC1966 as a resistance source, a protein putatively having polysaccharide hydrolase activity termed VrD1 was isolated, which inhibited the development of C. maculatus into adults when used in artificial seeds [ 14 ]. A 4-week feeding study on mice comparing a commercial mungbean line with an isogenic line containing the bruchid resistance gene from TC1966 showed no negative impact on growth or any pathological effect of the V. radiata var.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that millets contain a wide range of phenolic compounds (Chandrasekara & Shahidi, 2012;Chethan & Malleshi, 2007;Naczk & Shahidi, 2004;Udeh et al, 2017). Previous studies have reported the effects in a number of seeds of several defensive chemicals and proteins such as cyclopeptide alkaloid, trypsin, peptide compound "GIF-5," and cysteine-rich protein on several beetle species (Chan, Chen, & Horng, 2005;Chen, Lin, Kuan, Sung, & Chen, 2002;Kaga, Teraishi, Iijima, Sugawara, & Ishimoto, 2000;Sugawara et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Low adult emergence, prolonged development period, and reduced body mass of bruchids have been observed in common bean and cowpea genotypes that exhibit antibiosis-type resistance (Lin et al 2005;Velten et al 2007a, b;Eduardo et al 2016). The low rate of bean weevil emergence in the UFAC-Q01 cowpea variety and in the UFAC-R01 common bean variety may be related to the occurrence of antibiosis as a resistance mechanism in these varieties, which is usually characterized by high larval mortality (Baldin & Lara 2004).…”
Section: Discussionmentioning
confidence: 99%